Alpha-tricalcium phosphate cement in the reconstruction of bone defects in rats - Pinto,João Gabriel Souza (2011)
PURPOSE: To evaluate the ability of a mixture of α-TCP and autogenous bone (AB) vs. α-TCP alone and AB alone to promote new bone formation and tissue repair in bone defects. METHODS: Bone defects surgically created in 15 male Wistar rats were divided into four groups: Group I (AB), Group II (α-TCP), Group III (α-TCP+AB assessed by light microscopy), and Group IV (α-TCP+AB assessed by scanning electron microscopy). Bone repair findings were assessed at 30, 60, and 120 days postoperatively. RESULTS: The histological findings obtained in Groups I (p=0.459), II (p=0.368), and III (p=0.459) and at 30 days (p=0.717), 60 days (p=0.717), and 120 days (p=0.779) did not show statistically significant differences. Scanning electron microscopy revealed direct contact between the α-TCP+AB implant and the bone tissue at 120 days. CONCLUSION: The α-TCP implant is effective alternative bone substitutes for the treatment of critical size bone defects.